The determinant factor of the mother's ability to choose healthy food - Nurul Ridhi Utami; Endang Mulyatiningsih (Jurnal Pendidikan Vokasi, 2021)
This study aims to reveal: 1.) The size of the capital city in consuming healthy food; 2.) Selection of healthy food between working and non-working mothers; 3.) Choosing mothers in healthy food between families with a budget for food costs per person per day; and 4.) Choosing mothers in healthy food according to the number of family members. This research is a quantitative survey. The population was the research of PKK mothers in Delta Pawan and Benua Kayong districts, Ketapang, West Kalimantan. Samples of 90 can be responsive using cluster area random sampling. Validity is based on content validity. The reliability of the instrument was calculated using the Guttman Split-half. Data analysis used descriptive and comparative analysis of K sample one way ANOVA. The results showed that: 1.) The choice of mothers in healthy food consumption was seen from the high category knowledge with a frequency of 58.8%. Attitude category is sufficient with a frequency of 52.2%, high category skills with a frequency of 54.4%; 2.) There is a positive and significant difference in the selection of mothers who lack healthy food in terms of working and non-working mothers 0.003 < 0.05; 3.) There is a positive and significant difference in the choice of mothers in healthy food consumption in terms of family income, namely the budget for food costs per day per person of 0.000 < 0.05; and 4.) There is a positive and significant difference in the choice of mothers in healthy food consumption in terms of family type, namely the number of family members of 0.003 < 0.05.